High TNF-α Levels in Active Phase Chronic Suppurative Otitis Media Caused by Gram-positive Bacteria - Dewi, Marisa Rizqiana; Pratiwi, Dewi; Kandhi, Putu Wijaya (Cell and BioPharmaceutical Institute, 2023)
Background: Chronic suppurative otitis media (CSOM) is a persistent inflammatory disease of the middle ear and mastoid cavity caused by pathogenic infection. CSOM has a fairly high incidence in developing countries and is the main cause of acquired hearing loss in children. Tumor necrosis factor alpha (TNF-α) is a significant inflammatory mediator in CSOM. This study aimed to analyze TNF-α levels in ear discharge and blood serum in active phase CSOM caused by Gram-positive and Gram-negative bacteria.Materials and Methods: This research was an analytical observational study with a cross sectional design. Blood serum and ear discharge from CSOM patients were used in this study. Blood serum and ear discharge TNF-α levels were measured using enzyme-linked immunosorbent assay.Results: From 26 CSOM subjects, 13 subjects were infected with Gram-positive bacteria and the 13 others were infected with Gram-negative bacteria. The majority of the subjects were male (53.8%) with an age range from 36-45 years (42.3%). The most common species of bacteria was Pseudomonas aeruginosa. Blood serum and ear discharge TNF-α levels were higher in samples that contained Gram-positive bacteria.Conclusion: TNF-α levels in active phase CSOM caused by Gram-positive bacteria are higher than those which are caused by Gram-negative bacteria.Keywords: chronic suppurative otitis media, TNF-α, gram-positive, gram-negative